The effects of the interaction of technology, structure, and organizational climate on job satisgfaction - Ibrahim Ali,; Juhary Haji Ali, (Sunway University College, 2005)
This study examines the effects of the interaction of technology, structure, and organizational climate on job satisfaction in power-generation plants. Correlation tests and series of hierarchical regression analyses were performed. The study reveals several significant correlations among these three organizational variables and with employee job satisfaction.